Technique on simulation for real time oil palm fruits maturity prediction - Razali, Mohd Hudzari; Wan Ismail, Wan Ishak; Ramli, Abdul Rahman; Sulaiman, Md. Nasir; Harun, Mohd Haniff (Academic Journals, 2011)
This paper introduces the new method of procedure in studying the relationship of the mesocarp oil content with the skin colour of oil palm fruit in respect to its maturity. The procedure started after collecting the fruitlets sample from fresh fruit bunches (FFB) during unripe, until overripe stage. The variety of oil palm is Pisifera (Dura X Tenera). The images on each three age categories of FFB were captured at monitoring area with setting image parameter. NIKON coolpix4500 digital camera with tele converter zooming device was used to capture the image. Subsequently, after the end of the capturing session, the fruitlets were pulled from FFB and sent to analyse for oil mesocarp content. The Soxhlet Extractor Soxhlet apparatus is used to determine the oil content of the fruit based on the experiment of standard bunch analysis procedure. The image will be analysed for optical properties of colour, using developed analysis Graphical User Interface (GUI). Using regression analysis of polynomial 2nd order method, it shows that the optical property of oil palm fruit was significant in determining the oil mesocarp fruit with respect to its degree of maturity.